Space 2006 2006
DOI: 10.2514/6.2006-7489
|View full text |Cite
|
Sign up to set email alerts
|

The Mir Crew Safety Record: Implications for Space Colonization

Abstract: [Abstract] In 1985, Rockwell International (now Boeing-North American) completed the Space Station Crew Safety Alternatives Study for NASA. This five-volume study identified a wide range of potential safety threats and hazards that the crew might encounter on the future International Space Station. These threats included fire, explosion, collision, decompression, contamination, and radiation, among many others. One volume focused on the human factors aspects of safety, featuring the Crew Safety-Human Factors I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Mission commander, astronaut Bob Overmyer, indicated that Wang was depressed over the failure of his experiment (Reichhardt, 2002). Similarly, after receiving the news of his mother's passing, Mir 18 Commander Vladimir Dezhurov separated from the crew and secluded himself in a module for days (Dudley-Rowley, 2006). Despite the emotional toll of losing a parent, extreme response to grief may be influenced by compromised emotion regulation processes.…”
Section: Mood and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Mission commander, astronaut Bob Overmyer, indicated that Wang was depressed over the failure of his experiment (Reichhardt, 2002). Similarly, after receiving the news of his mother's passing, Mir 18 Commander Vladimir Dezhurov separated from the crew and secluded himself in a module for days (Dudley-Rowley, 2006). Despite the emotional toll of losing a parent, extreme response to grief may be influenced by compromised emotion regulation processes.…”
Section: Mood and Behaviormentioning
confidence: 99%
“…For example, both American and Russian psychologists expressed concerns regarding astronaut John Blaha's readiness for a long-duration mission on the Mir. And indeed, Blaha was later reported to experience depression and anger bursts during the mission (Dudley-Rowley, 2006). Given advancements in measures and greater access to more comprehensive sets of behavioral, cognitive, and neural data, psychological screening should adopt a neuropsychological approach and integrate the multitude of information sources to draw more informed conclusions and make more accurate predictions about astronauts' strengths, weaknesses, and potential risks.…”
Section: Future Research and Clinical Directionsmentioning
confidence: 99%
“…Examples include territoriality; volume limitations or overcrowding; noise; housekeeping issues; hygiene/cleanliness problems; life support issues in a closed atmospheric system; confinement, isolation, and separation; scheduling and coordination conflicts; boredom and monotony; lighting issues (as previously discussed); and emotional outbursts and mental illness. 12 The pre-launch planning and training process can eliminate some of these problems and reduce the severity of others.…”
Section: Space Ecosystems and Ecologiesmentioning
confidence: 99%
“…The paradigm shift in Mars planning and design cognition that would have occurred in the 1980s and 1990s had the Apollo program continued has not yet happened. NASA mission planners and designers were still demonstrating short-duration cognition during the NASA-Mir missions of the 1995-1998 (Burrough 1998, 7 Dudley-Rowley 2006 8 ). However, long-duration planning and design cognition means more than "duration."…”
Section: History Of Ideasmentioning
confidence: 99%